1992
DOI: 10.1128/jb.174.12.4189-4192.1992
|View full text |Cite
|
Sign up to set email alerts
|

Purification and some properties of sulfite:ferric ion oxidoreductase from Thiobacillus ferrooxidans

Abstract: Sulfite:ferric ion oxidoreductase in the plasma membrane of Thiobaciusferrooxidans AP19-3 was purified to an electrophoretically homogeneous state. The enzyme had an apparent molecular weight of 650,000 and was composed of two subunits (M1s, 61,000 and 59,000) as estimated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The Michaelis constants of sulfite:ferric ion oxidoreductase for Fe3' and sulfite ions were 1.0 and 0.071 mM, respectively. Sulfite:ferric ion oxidoreductase suffered from end pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 25 publications
2
47
0
1
Order By: Relevance
“…However, neither T. thiooxidans (169) nor T. ferrooxidans (277,303) was able to obtain energy to support growth from sulfur oxidation coupled to Fe(III) reduction. A hydrogen sulfideferric ion oxidoreductase involved in sulfur oxidation has been purified (300,301). T. thiooxidans (325) and T. ferrooxidans (302) also oxidized sulfur with the reduction of Mn(IV).…”
Section: Sulfur-oxidizing Fe(iii) and Mn(iv) Reducersmentioning
confidence: 99%
“…However, neither T. thiooxidans (169) nor T. ferrooxidans (277,303) was able to obtain energy to support growth from sulfur oxidation coupled to Fe(III) reduction. A hydrogen sulfideferric ion oxidoreductase involved in sulfur oxidation has been purified (300,301). T. thiooxidans (325) and T. ferrooxidans (302) also oxidized sulfur with the reduction of Mn(IV).…”
Section: Sulfur-oxidizing Fe(iii) and Mn(iv) Reducersmentioning
confidence: 99%
“…Although the transfer of electrons from ferrous iron to oxygen has not been conclusively established, the electron transfer pathway is thought to involve two cytochromes c (Cyc2 and Cyc1), a rusticyanin, and an aa 3 -type cytochrome c oxidase. [4][5][6] On the other hand, although some enzyme activities thought to be involved in the aerobic oxidation of elemental sulfur by A. ferrooxidans were detected, [7][8][9][10][11][12][13][14][15][16] the oxidation pathway of elemental sulfur has not yet been clearly elucidated.…”
mentioning
confidence: 99%
“…We have found that both iron oxidase and hydrogen sulfide:ferric ion oxidoreductase (SFORase) [12][13][14][15][16][17][18][19][20] are crucial in Cu-bioleaching by A. ferrooxidans AP19-3, 21) but when the levels of iron oxidase, SFORase, and Cu-bioleaching activities were compared among 67 strains of iron-oxidizing bacteria isolated from natural environments, no significant differences were observed in growth rates in iron medium or in the levels of cellular iron oxidase activity in the cells. However, a y To whom correspondence should be addressed.…”
Section: Isolation and Characterization Of Acidithiobacillus Ferrooximentioning
confidence: 99%
“…In this study, we found for the first time that A. ferrooxidans strain D3-2 has a unique sulfite oxidase resistant to a high concentration of sulfite ion that shows maximum activity at 8 mM of sodium bisulfate, while A. ferrooxidans ATCC 23270 has a sulfite oxidase sensitive to sulfite ion that is completely inhibited by 1 mM of sodium bisulfite. Since it is known that sulfite ion is a toxic intermediate during sulfur oxidation in A. ferrooxidans cells and, that it strongly inhibits iron oxidase activity, [12][13][14][15]18,19,[23][24][25][26][27] A. ferrooxidans strains that have a sulfite resistant-sulfite oxidase are supposedly able to grow and solubilize more copper from chalcopyrite (CuFeS 2 ) than strain ATCC 23270, which has a sulfite-sensitive sulfite oxidase, because in the bioleaching process, A. ferrooxidans cells must coexist for a long time, more than a month, with toxic sulfite ions produced by the oxidation of CuFeS 2 . In this study, we also found for the first time that strain D3-2, but not strain ATCC 23270, grew and solubilized Cu 2þ in 1% chalcopyrite-concentrate medium supplemented with 5 mM of sodium bisulfite.…”
Section: Isolation and Characterization Of Acidithiobacillus Ferrooximentioning
confidence: 99%